Pengaruh Product Variety, Online Customer Review dan Fear of Missing Out (FOMO) Terhadap Impulse Buying Brand Glad2glow pada Platform Tiktok - Tri Indah Susilowati; Maruji Pakpahan; Yugi Setyarko (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
This study aims to analyze the influence of product variety, online customer reviews, and Fear of Missing Out (FOMO) on impulse buying behavior for Glad2Glow brand products on the TikTok platform. This study uses a quantitative approach with an associative research design. The population in this study is not precisely known, so the sample was determined using a non-probability sampling technique with the Lemeshow formula, resulting in 105 respondents as the research sample. Data were collected by distributing questionnaires to TikTok users who had purchased Glad2Glow products. Next, the data were analyzed using statistical software to test validity, reliability, and the influence between variables through multiple linear regression analysis. The results showed that partially, product variety had a positive and significant effect on impulse buying, meaning that the more diverse the products offered, the higher the tendency for impulsive buying. Online customer reviews were also shown to have a positive and significant effect, demonstrating the importance of information and experiences of other consumers in triggering spontaneous purchasing decisions. In addition, FOMO had a positive and significant effect on impulse buying, indicating that the psychological drive to keep up with trends also increases consumptive behavior. Simultaneously, these three variables had a positive and significant effect on impulse buying.